The Analysis of Sperm Donor Insemination Based on Perspective of Islamic Criminal Law - Nasiri, Nasiri (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2023)
Insemination of donor sperm is an interesting subject to study. There is a chance that the child from the donor's sperm will not be recognized by the parents if it is different from expectations. Therefore, in terms of recognition, both in terms of positive law and Islamic law, it is an interesting problem to study.The aims of this study are: (1) to find out Islamic criminal law views on donor sperm insemination; (2) to find out the form of sanctions insemination of donor sperm according to Islamic criminal law. The design used in this study was normative legal research with a (statute approach) from the perspective of Islamic criminal law. In this study, documentation data collection techniques were used. Analysis technique normative legal research,used was descriptive-analysis with evaluation, interpretive, construction, and content analysis.Islamic criminal law views on donor sperm insemination is haram (forbidden) in Islamic perspective. The law is the same as adultery and children born from this kind of insemination have the same status as children born outside of a legal marriage. Perspective of Islamic criminal law on perpetrators. Artificial insemination with donor sperm cells is not restricted as is the law of fornication in adultery, however, artificial insemination with donor sperm is ta'zir on the grounds that the elements in the hadd of adultery are not fulfilled because there is no direct sexual intercourse.